Bonus Taxes and International Competition for Bank Managers - Daniel Gietl; Andreas Haufler (Center for Economic Studies and ifo Institute (CESifo), 2017)
We analyze the competition in bonus taxation when banks compensate their managers by means of fixed and incentive pay and bankers are internationally mobile. Banks choose bonus payments that induce excessive managerial risk-taking to maximize their private benefits of existing government bailout guarantees. In this setting the international competition in bonus taxes may feature a `race to the bottom' or a `race to the top', depending on whether bankers are a source of net positive tax revenue or inflict net fiscal losses on taxpayers as a result of incentive pay. A `race to the top' becomes more likely when governments' impose only lax capital requirements on banks, whereas a `race to the bottom' is more likely when bank losses are partly collectivized in a banking union.
Keywords: H20; H87; G28; 330; bonus taxes; international tax competiton; migration